Pemetaan Model Penerapan Murabahah Di Perbankan Syariah: Analisis Terhadap Konsistensi Fiqih Muamalah Dan Implikasi Akad Wakalah - Syamsurijal; fitri sariningsih (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2024)
This study investigates the model of implementing murabahah contracts in Islamic financial institutions, focusing on consistency with the principles of muamalah fiqh and the implications of wakalah contracts. The research method used is descriptive and qualitative analysis of various legal documents, sharia literature, and field practices in Islamic banking. The results of this research show that there are three models of murabahah application in the Islamic banking industry. The first model followed muamalah fiqh consistently. The second model is almost similar to the first model, but there are differences related to direct ownership of goods from suppliers to customers and payments made directly by banks to sellers. While the third model involves customers in a Murabahah contract with the bank, while customers also make a wakalah contract to buy their own goods. The third model is currently widely discussed because the Murabahah contract is carried out without ownership of goods by the bank, even though ownership itself is a legal condition of murabahah according to DSN-MUI. In this finding, the murabahah contract and the wakalah contract are carried out simultaneously without the goods belonging to the bank first.